Zonificación agrícola de riesgos climáticos para el cultivo de quinua (Chenopodium quinoa Willd) en el Altiplano Peruano: Agricultural zoning of climatic risks for quinoa (Chenopodium quinoa Willd) cultivation in the Peruvian Altiplano - Yzarra-Tito, Wilfredo Julián (2025)
The objective of this study was to conduct agricultural zoning of climate risk for quinoa cultivation. Data from 38 meteorological stations of the National Meteorology and Hydrology Service in Puno region were used. The zoning was based on the development of the water balance model, applying the water requirement satisfaction index (ISNA), for two levels of soil available water capacity (115 mm/m and 145 mm/m). Spatial analysis of the ETr/ETm ratio, obtained from the SARRAZON model, was carried out for each phenological stage through frequency analysis of ISNA values. These data were processed in ArcGIS10.0, using the ordinary kriging interpolation method. Once the maps were generated, they were clipped to the quinoa production zones of the region and classified as follows: for Phase I: low risk (ISNA ≥ 0.65); medium risk (0.55 < ISNA < 0.65) and high risk (ISNA ≤ 0.55), considered for the emergency stage; and for phase III the following ranges were considered: low risk (ISNA ≥ 0.55); medium risk (0.45 < ISNA < 0.55) and high risk (ISNA ≤ 0.45) during flowering and grain filling. September was identified as the month with the highest exposure to climate risk; October presented intermediate conditions; and November was the safest month, showing a predominance of low-risk zones: However, late sowing may expose the crop to critical water deficits during the final phases of quinoa cultivation.